Two new species of Monstrilla (Copepoda: Monstrilloida: Monstrillidae) from a protected reef system of the Mexican Caribbean - Eduardo Suárez-Morales (European Journal of Taxonomy, 2024)
Several adult female monstrilloid copepods, collected in March 2022 from the protected reef area of Xcalak, on the southern part of the Mexican Caribbean coast, proved to belong to two undescribed species of Monstrilla Dana, 1849. They are described here as M. xcalakensis sp. nov. and M. annulata sp. nov., partly by use of scanning electron microscopy. Females of the two species are generally similar but differ in: (1) antennular segmental structure, (2) antennular armature and ornamentation, (3) structure and setation of the fifth leg, (4) number and modifications of the caudal setae, and (5) integumental ornamentation. Comparison with congeneric species revealed distinctive features for both species that support their status as new. These two species are interesting additions to the reef-dwelling monstrilloid copepod fauna of the Mexican Caribbean and confirm Monstrilla as the most diverse genus of monstrilloids in this area, now represented by nine species.